Hukuman dan Ganjaran Berdasarkan Hadis Nabi Muhammad SAW dalam Pendidikan - Coil, Coil; Charles, Charles (Lembaga Yasin AlSys, 2023)
Students are motivated to learn when using rewards and punishments as teaching methods. Thus, the goals and objectives of rewarding and punishing students are to raise their desire to do better and to be more active in carrying out the positive activities they have already done, including the development of student-worthy morals. In order to be effective, rewards and penalties must be used in teaching. Rewards are given to pupils in recognition of their accomplishments or good deeds, whereas punishment has a deterrent impact on rule-breaking on the part of students. It is important to keep in mind that punishment does not involve suffering and instead encourages individuals to develop their independence. It's crucial to use both rewards and penalties to teach children. Students are motivated to learn when using rewards and punishments as teaching methods. Thus, the goals and objectives of rewarding and punishing students are to raise their desire to do better and to be more active in carrying out the positive activities they have already done, including the development of student-worthy morals. Teachers are expected to administer incentives and penalties in accordance with the law so that students would accept them wholeheartedly. And it is hoped that there won't be any miscommunication between teachers and students as long as rewards and penalties are given. In order for the use of rewards and penalties to benefit pupils and improve them, particularly in terms of morality.